PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF STAD UNTUK MENINGKATKAN KUALITAS DAN HASIL BELAJAR ALAT UKUR SISWA DI KELAS X TEKNIK BISNIS SEPEDA MOTOR SMK NEGERI 1 SUMATERA BARAT SEMESTER GENAP TAHUN PELAJARAN 2020/2021 - Nismah Nismah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
This research is motivated by the low learning outcomes of student measuring instruments. The influencing factor is that students are not accustomed to working on assignments in group discussions. To overcome this problem, one of them is by applying the STAD cooperative learning model. This study aims to determine the effect of the implementation of the STAD cooperative learning model on the activities and learning outcomes of the class X students of Motorcycle Business Engineering at SMK N 1 West Sumatra. This research is a classroom action research. Based on the learning outcomes test, the students' mastery scores in the first cycle were obtained.